A comparative case study of Reserve Deputies in a Florida sheriff's office and Special Constables in an English police force. (December 2018) - Britton, Iain; Wolf, Ross; Callender, Matthew
Volunteers operating as 'sworn' police personnel with full policing powers are a common feature of policing organizations in many countries, including Special Constables in the UK and Reserve and Auxiliary police officers and deputy sheriffs in many law enforcement agencies in the USA. There has been only limited research into the experience of serving as a volunteer in such policing roles in either the US or UK settings, together with very little comparative research into volunteer officer experience across different international settings. This article presents a small-scale, comparative qualitative case study based upon interviews with volunteers from a Reserve Unit in a sheriff's office in Florida and with volunteer Special Constables from an English police force, exploring their perspectives and experiences of volunteering in their respective policing organizations. The research identifies key differences between the settings in respect of past experience and volunteer pathways, models of training and confidence of operational capability, development and management of roles, the opportunities to develop specialization for volunteers, and leadership. The article points to the value of comparative research in police voluntarism and calls for more research in this area.